MIWT Global Resources Sdn Bhd / Zabir Brahim Baharudin - Baharudin, Zabir Brahim (Universiti Teknologi MARA, Sarawak, 2018)
In line with the rise of construction, oil and gas industries, M.I.W.T Global Resources Sdn. Bhd. was established on 5th June 2013 under Companies Act 1965 as an approved training provider under the Malaysian Human Resource Development Fund (HRDF) for semi-skilled or unskilled local employees, semiskilled or unskilled foreign employees, school leavers, and youth interested in pursuing their career in construction, oil and gas industries.